2013
DOI: 10.5586/asbp.2013.020
|View full text |Cite
|
Sign up to set email alerts
|

The effect of seedling chilling on glutathione content, catalase and peroxidase activity in Brassica oleracea L. var. italica

Abstract: IntroductionProper growth and development of plants depends on an efficient defense system, mainly against reactive oxygen species. Studies on how plant genotypes respond to all kind of stresses indicate a similar mechanism of adaptation to unfavorable environmental conditions. These reactions are mostly connected with neutralizing free radicals, particularly reactive oxygen species (ROS) which frequently appear as the effect of different stress factors [1][2][3]. Many experiments indicate significance changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…A significant increase in the level of glutathione was observed in the seedlings of broccoli subjected to cold conditions. 10 The content of glutathione increased significantly after heat stress in the seedlings of B. juncea . 5…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…A significant increase in the level of glutathione was observed in the seedlings of broccoli subjected to cold conditions. 10 The content of glutathione increased significantly after heat stress in the seedlings of B. juncea . 5…”
Section: Resultsmentioning
confidence: 93%
“…The most active enzymes in response to environmental stressful conditions are CAT and SOD. 10 SOD is usually considered as the first line of defense against oxidative stress. 11 This enzyme catalyzes the partitioning of O 2 – into either an ordinary molecular O 2 or into H 2 O 2 , which is also damaging, but less so, and is degraded by other enzymes such as APX or CAT.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the substrate for CAT activity is H 2 O 2 , a by-product of SOD action, their functions should be coupled to achieve a synergistic effect on stress tolerance (Xu et al, 2014). Published studies also confirmed that cold stress increased catalase and superoxide dismutase activity in B. oleracea (Soengas et al, 2018;Wojciechowska et al, 2013). Another study on sweet potato (Ipomoea batatas) indicated Overexpression of IbCAT2 gave salt and drought tolerance in Escherichia coli and Saccharomyces cerevisiae.…”
Section: The Expression Patterns Of the Bncsd1 And Bncat1mentioning
confidence: 95%